Principles of Preventive Police Activity: Concepts, Content and Their Classification - S. O. Shatrava; H. R. Parkhanov (Law and Safety)
The author of the article has studied the scientific positions of scholars on understanding and classification of the principles of law. The characteristic features of the principles of preventive police activity have been distinguished. First of all, they are formed and developed in accordance with the contemporary requirements, expectations and needs of members of society and the state regarding the protection of their rights, freedoms and interests within the public and legal sphere; secondly, they determine the social purpose, nature, content and limits of preventive police activity; thirdly, it is obvious that all principles of preventive police activity form an objectively conditioned, normatively fixed, scientifically sound, relatively stable “coordinate system”, the elements of which do not act in isolation but, in a certain interdependence, do not contradict each other and have distinct character in the application of police preventive measures and the implementation of the preventive function by the agencies and units of the National Police of Ukraine.